2011
DOI: 10.2337/dc10-2264
|View full text |Cite
|
Sign up to set email alerts
|

First-Trimester Circulating 25-Hydroxyvitamin D Levels and Development of Gestational Diabetes Mellitus

Abstract: OBJECTIVETo investigate the association between first-trimester maternal serum levels of 25-hydroxyvitamin D (25-OH-D) as measured by liquid chromatography-tandem mass spectrometry and development of gestational diabetes mellitus (GDM).RESEARCH DESIGN AND METHODSWe conducted a case-control study involving 248 women in the first-trimester of pregnancy, 90 of whom developed GDM and 158 remained normoglycemic.RESULTSAlthough booking 25-OH-D levels correlated negatively with 2-h glucose post-oral glucose tolerance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
100
4
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(114 citation statements)
references
References 10 publications
(12 reference statements)
8
100
4
2
Order By: Relevance
“…20,10 In a retrospective study, Makgoba reported no significant differences in serum level of vitamin D in GDM and non-GDM pregnant women. 11 These situations are consistent with the findings of the current study. Indeed, we could not find any association between the maternal serum 25(OH) D status and the risk of GDM.…”
Section: Discussionsupporting
confidence: 83%
“…20,10 In a retrospective study, Makgoba reported no significant differences in serum level of vitamin D in GDM and non-GDM pregnant women. 11 These situations are consistent with the findings of the current study. Indeed, we could not find any association between the maternal serum 25(OH) D status and the risk of GDM.…”
Section: Discussionsupporting
confidence: 83%
“…Zhang et al (25) found that women with vitamin D deficiency during early pregnancy had a 3.7-fold increased risk of developing GDM compared with those who were vitamin D replete. However, other studies that have evaluated first-trimester vitamin D status and the subsequent risk of GDM have not found an association (30)(31)(32). Among these negative studies, none had information on vitamin supplementation and one was underpowered for the outcome.…”
Section: Discussionmentioning
confidence: 95%
“…The results do not support the notion that 25(OH)D concentration in the first term of pregnancy will be a good parameter to assess the risk of GDM in later gestation. The published prospective studies contain contrary opinions with respect to the connection between a low 25(OH)D concentration in the first term of gestation and the risk of developing GDM [14][15][16].…”
Section: Discussionmentioning
confidence: 88%
“…There were no other associations between 25(OH)D levels and maternal outcomes; however among women with 25(OH)D deficiency, 30-minute glucose concentrations were inversely associated with 25(OH)D concentrations [9]. A study completed in Great Britain found a negative correlation between the 25(OH)D concentration measured in the first term of pregnancy and 2-h glucose concentration during OGTT, although the former factor was unrelated to the risk of GDM development [14]. The assessment of the relationship between 25(OH)D and glucose metabolism in the European and South Asian populations showed a weak inverse correlation between 25(OH)D concentration and fasting glucose, as well as lack of correlation with fasting insulin level, glycaemia values in OGCT or GDM [15].…”
Section: Discussionmentioning
confidence: 99%